Fetal haemoglobin and early manifestations of homozygous sickle cell disease. Issue 4 (April 1992) - Bailey, K; Morris, J S; Thomas, P; Serjeant, G R
Abstract : The relevance of fetal haemoglobin (HbF) concentration to the development of early clinical manifestations of homozygous sickle (SS) disease has been investigated by examining the time to first occurrence and the proportional hazard of these complications in three groups of the HbF distribution at age 5 years. HbF was significantly related to dactylitis, painful crises, acute chest syndrome, and acute splenic sequestration. The relationship suggested that a critically low HbF concentration increased the risk, little difference in risk occurring between the medium and high HbF groups. The abdominal painful crisis and hypersplenism were not related to HbF concentration suggesting that the degree of sickling may not be important in their genesis. Parental education on acute splenic sequestration should be focused on children with HbF concentrations in the lowest part of the HbF distribution for age.